PERANCANGAN KATALOG PANDUAN WISATA SERIBU RUMAH GADANG DI KABUPATEN SOLOK SELATAN - REVIL HUDRIANI, Hendra Ariwan, S.Sn., M.Sn Drs. Ariusmedi, M.Sn. (DEKAVE : Jurnal Desain Komunikasi Visual, 2019)
Gadang tourism is a thousand houses icons kabupaten solok seed south.The gadang in the area of a thousand houses gadang this generally hundreds of years, even some of them have been built since 1700-an.Even though has modified several times, restoration council but characteristic and the  original form at all unchanged.When gadang-rumah gadang generally the house in some parts of other minangkabau is almost extinctThe catalogue is one of the media that effective and communicative in communicating information easily and interesting to target an audience.The purpose of this catalogue is to give information on about the area of a thousand houses gadang overall, so that this catalogue can as a guide by  travelers.A method of designing the gadang a thousand houses in a glass box ( glass box ) method .This  method chosen karen abersifat systematic and rational and very effective in the design catalog area a thousand houses gadang tourist guideKeyword: catalog , reribu gadang house , tourism glass box method